Media and Accountability in Latin America Framework - Conditions - Instruments - Bastian, Mariella; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2019)
This study approaches a pressing question for the public, the media, and in academia: how can the media be held accountable? By focusing on the relationship between media and accountability in the understudied region of Latin America, Mariella Bastian provides a theoretical framework for the analysis of media accountability (MA) beyond the Global North. The underlying conditions for the development of MA in Brazil, Argentina, and Uruguay are identified by conducting a multi-method study. The author also gives an overview of the status quo of the implementation of both traditional and innovative MA instruments. Content Brazil, Argentina, Uruguay: Background and media landscapes De-westernizing the media accountability approach: Towards a Latin American design of accountability frames Conditions for media accountability in Latin America The status quo of online media accountability in Latin America Media accountability instruments in Brazil, Argentina, and Uruguay Special cases and typology of media accountability instruments in Latin America Target Groups Lecturers and students of journalism studies, communication science, Latin American studies, political sciences Journalists, media-related NGOs, policy makers The Author Dr. Mariella Bastian is a postdoctoral researcher at the Institute for Information Law (University of Amsterdam). Her research interests include media accountability, media ethics, news personalization, Latin American media systems, media & democracy, and international journalism. .
Brazil, Argentina, Uruguay: Background and media landscapes -- De-westernizing the media accountability approach: Towards a Latin American design of accountability frames -- Conditions for media accountability in Latin America -- The status quo of online media accountability in Latin America -- Media accountability instruments in Brazil, Argentina, and Uruguay -- Special cases and typology of media accountability instruments in Latin America.
Keywords: Journalism; Mass media; Culture -- Study and teaching; Journalism; Media Sociology; Cultural Studies